The Influence of Leadership, Interpersonal Communication and Team Effectiveness on The Performance of Al Washliyah University UNIVA Medan Lecturers - Syahri, Putri; Siahaan, Amiruddin; Daulay, Nurussakinah (Tadbir : Jurnal Studi Manajemen Pendidikan, 2025)
This study aims to answer the problems of the eight hypotheses proposed, namely: 1) The effect of leadership on lecturer performance, 2) The effect of leadership and interpersonal communication on lecturer performance, 3) The effect of interpersonal communication on lecturer performance, 4) Effect of leadership on team effectiveness, 5) Effect of interpersonal communication on team effectiveness, 6) Effect of team effectiveness on lecturer performance, 7) The effect of leadership, interpersonal communication, and team effectiveness on lecturer performance, and 8) The role of team effectiveness mediates the influence between leadership and interpersonal communication on lecturer performance. The population of this study were all lecturers of Al Washliyah University UNIVA Medan as many as 210 people with a total sample of 136 taken by proportional random sampling technique based on the Krejcle and Morgan Tables which were processed using SPSS and analysed by Path Analysis. The instrument used is a questionnaire. The results of the analysis show that leadership has a significant direct effect on the performance of UNIVA Medan lecturers by 0.465. 2) Leadership and interpersonal communication have a significant direct effect on the performance of UNIVA Medan lecturers by 0.371. 3) Interpersonal communication of lecturers has a significant direct effect on the performance of UNIVA Medan lecturers by 0.675. 4) Leadership has a significant direct effect on team effectiveness at UNIVA Medan by 0.437. 5) Interpersonal communication has a significant direct effect on team effectiveness at UNIVA Medan by 0.594. 6) Team effectiveness has a significant direct effect on the performance of UNIVA Medan lecturers by 0.808. 7) Team effectiveness mediates the influence between leadership and interpersonal communication on the performance of UNIVA Medan lecturers by 0.373. 8) Leadership, interpersonal communication and team effectiveness together on the performance of UNIVA Medan lecturers by 73.7% while the rest comes from the influence of other variables outside the variables used in this study.